2021
DOI: 10.1016/j.worlddev.2020.105128
|View full text |Cite
|
Sign up to set email alerts
|

Responding to COVID-19: Community volunteerism and coproduction in China

Abstract: Highlights Communities can respond to COVID-19 by mobilizing volunteers to coproduce services. Long-term alliances between civic groups and governments enable volunteer action. In the first wave, volunteers shifted to COVID relief, crowding out other causes. Mobile technology and prior crisis experience galvinized professional volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
122
0
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 40 publications
2
122
0
8
Order By: Relevance
“…This may be of particular importance when collective quarantine measures are enforced and action is mostly confined to the digital sphere. Some have indeed suggested that digital platforms played a key role in mitigating the effects of the COVID-19 pandemic (Miao, Schwarz, & Schwarz, 2021).…”
mentioning
confidence: 99%
“…This may be of particular importance when collective quarantine measures are enforced and action is mostly confined to the digital sphere. Some have indeed suggested that digital platforms played a key role in mitigating the effects of the COVID-19 pandemic (Miao, Schwarz, & Schwarz, 2021).…”
mentioning
confidence: 99%
“…Volunteering is a key component of coproduction, since volunteer coworkers actively provide community services to their communities at no cost. In the conditions of socio-economic instability, the participation of coproducers in the sale of public services becomes the most relevant-"the COVID-19 pandemic created a critical need for citizen volunteers working with government to protect public health and to augment overwhelmed public services" [46].…”
Section: Theoretical Approaches To Governmental Support For Volunteeringmentioning
confidence: 99%
“…If these conditions are not met, it cannot be assumed that coproduction will be successful [48]. The leading role of the state in creating these conditions and developing volunteering from above is an example of top-down and state-driven coproduction that differs from the bottom-up coproduction [46].…”
Section: Theoretical Approaches To Governmental Support For Volunteeringmentioning
confidence: 99%
“…Environmental events, accidents, pandemics, and major infrastructure decisions, for example, give rise to a broad expression of citizen concerns. Increasingly, given technological and demographic shifts, such participation occurs via online conduits such as blogs and social networking platforms (Liu et al, 2017;Miao et al, 2021). Social media political participation has the potential both to inform effective policy making and to challenge government stability, depending in large part on the official response (Mayer-Schönberger & Lazer, 2007).…”
Section: Introductionmentioning
confidence: 99%